Edukasi dan Promosi Kesehatan Tentang Jumlah Perdarahan Kala IV di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2024 - Ika Damayanti Sipayung; Lasria Simamora (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
One of the global targets of MGDS is to reduce maternal mortality and neonatal mortality. The maternal mortality rate in Indonesia is still high at 390 per 100,000 live births. Referring to the relationship between birth management and various treatments, the biggest cause of maternal mortality is postpartum hemorrhage. Efforts have been made in problems related to bleeding, even several studies have conducted IMD in handling bleeding problems considering that IMD can affect the oxytocin hormone associated with bleeding. The purpose of this study was to see how IMD affects the amount of bleeding in the fourth stage. This study was a Quasi Experiment using primary data. The population and sample were all primiparous mothers totaling 46 respondents using the Purposive Sampling method. Data were analyzed univariately and bivariately using the Independent t-test. The results showed that there was a significant effect between IMD and the amount of bleeding in the fourth stage. The average amount of bleeding in the fourth stage of respondents who underwent Early Breastfeeding Initiation was 150.63 with a standard deviation of 22.149. Meanwhile, respondents who did not undergo Early Breastfeeding Initiation had an average of 166.09 bleeding in the fourth stage with a standard deviation of 21.580. The statistical test obtained a P value of 0.000. With this study, it is clear that there is an effect of IMD on the amount of bleeding in the fourth stage of labor. Midwives and doctors are expected to implement IMD to reduce maternal and infant morbidity and mortality.